Evaluation of 0.12% chlorexidine in intensive care unit patients: a randomized clinical trial - Helga Lucy Feitosa Santos Melo; Yasmin Alves do Nascimento; Mônica Christine Alves Cabral Cardoso; Graziane Ribeiro Couto; Regiane Cristina do Amaral; José Augusto Santos da Silva; Ismário Silva de Meneses (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT Objective: To evaluate the antimicrobial effect of 0.12% aqueous chlorhexidine solution on the oral microbiota of patients on mechanical ventilation in Intensive Care Units (ICUs) at 6, 8 and 12 hours after oral hygiene. Methods: This is a randomized clinical trial in which 30 patients admitted to the ICUs of a philanthropic hospital based in Aracaju-SE, selected by spontaneous demand over a period of 2 months according to inclusion criteria, were randomized and equally distributed into three groups. Oral hygiene followed the disinfection protocol adopted by the hospital, the same recommended by the Brazilian Association of Intensive Medical Care (AMIB). Saliva samples were collected before the application of 0.12% chlorhexidine, shortly after application of the solution, and then after 6 hours (TEST 1 Group), 8 hours (TEST 2 Group) and 12 hours (CONTROL Group), according to each group. Results: The material was sent to a clinical analysis laboratory for microbiological evaluation using the bacterioscopy technique, also called Gram stain. The results were tabulated in spreadsheets and analyzed using the Friedman test between groups and Kruskal Wallis test between groups. Conclusion: The study showed no statistical difference between groups and between groups.